Equality-enhancing potential of novel forms of assisted gestation: Perspectives of reproductive rights advocates - Romanis, Elizabeth Chloe (Bioethics, 2023)
Novel forms of assisted gestation—uterus transplantation and artificial placentas—are highly anticipated in the ethico-legal literature for their capacity to enhance reproductive autonomy. There are also, however, significant challenges anticipated in the development of novel forms of assisted gestation. While there is a normative exploration of these challenges in the literature, there has not yet, to my knowledge, been empirical research undertaken to explore what reproductive rights organisations and advocates identify as potential benefits and challenges. This perspective is invaluable. These organisations/individuals have an awareness not only of the needs of individuals but also of the political landscape in which regulatory decisions are made and which individuals navigate when seeking reproductive assistance. In this study, data was generated from two semi-structured focus groups (n = 11). Reflective thematic analysis was used to examine the views raised by study participants in these focus groups. This paper explores two of the themes constructed in the data. First, the equality-enhancing potential of assisted gestation exploring the multifaceted ways in which assisted gestation has structural benefits for marginalised groups. Second, realising the equality-enhancing potential of assisted gestation explores the intersecting barriers to access to reproductive technologies and how they may impede the benefits of these technologies in practice. These results can enhance conceptual understanding of the importance of novel forms of assisted gestation and ensure that attention is paid to practical barriers in further normative research.